(untitled) (Global Journal of Human-Social Science, 2015)
Crime is an act against law and thus is a punishable offence. Crime varies over space and time. Among all crime types, murder is the most cruel and inhumane which do an irreparable damage to the society. The study attempts to examine how atmospheric warming may increase homicides. To achieve this, the paper analyses the trend pattern of homicides and various determinants. Social heterogeneity and weather-more specifically temperature, are considered to be most influencing in catalysing aggression and murder. The study tries to evaluate the linkages between these factors by examining the correlation between homicide and income and poverty level, level of urbanisation, and temperature in India over a 13-year span of time. The analysis is based mainly on the secondary data obtained from National Crime Record Bureau of India, India Meteorological Department and State and District Censuses. Results show that while poverty, urbanisation and income level do not affect the homicide significantly in unidirectional manner, temperature does affects the pattern of murder incidences. Interestingly the regions which have witnessed warming trend during the past decade, are also the areas of high and increasing homicide rates.